2016
DOI: 10.1371/journal.pone.0154647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Characterization of Cryptosporidium Species in Dairy Calves in Central Ethiopia

Abstract: The burden of cryptosporidiosis due to Cryptosporidium parvum is well documented in HIV-positive patients in Ethiopia. However, the role of animals in zoonotic transmission of the disease is poorly understood. The aim of this study was to determine the prevalence and genotypes of Cryptosporidium species in dairy calves; to assess the role of cattle in zoonotic transmission in central Ethiopia. A total of 449 fecal samples were collected and screened using modified Ziehl-Neelson staining method and PCR targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
23
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
8
23
2
3
Order By: Relevance
“…The results of a study conducted in Ethiopia by Wegayehu et al (2016) were similar to those found in our study. The animals were aged between three days and five months.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The results of a study conducted in Ethiopia by Wegayehu et al (2016) were similar to those found in our study. The animals were aged between three days and five months.…”
supporting
confidence: 90%
“…In epidemiological surveys conducted in China, India, Poland and Ethiopia, the average prevalence of Cryptosporidium spp. in young calves ranged from 5.6% to 17% (WANG et al, 2014;WEGAYEHU et al, 2016).…”
mentioning
confidence: 99%
“…For instance, reported prevalence values of C. parvum were 5% and 11% in healthy and diarrhoeic calves in Sweden (Bj€ orkman et al 2003), 40.6% in dairy calves from farms with a history of diarrhoea in Canada (Trotz-Williams et al 2005), or 25.68% and 50% in nondiarrhoeic and diarrhoeic neonatal dairy calves in India (Singh et al 2006). In addition to C. parvum, Cryptosporidium andersoni, Cryptosporidium bovis, Cryptosporidium ryanae and Cryptosporidium ubiquitum can also be identified in calves (Bj€ orkman et al 2015;Wegayehu et al 2016). Cryptosporidium parvum, C. ubiquitum, and C. andersoni are also recognised zoonotic agents, and persons in contact with infected cattle are at risk of contracting these infections (Jiang et al 2014;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of cryptosporidiosis can be carried out by using faecal smears stained by the modified Ziehl-Neelsen technique (Bj€ orkman et al 2003;Singh et al 2006;Wegayehu et al 2016), Sheather's sucrose flotation solution (Trotz-Williams et al 2005;Singh et al 2006) or direct immunofluorescence assays (DIA) (Bj€ orkman et al 2015;Mirhashemi et al 2015). Enzyme-linked immunosorbent assays (ELISA) are also available for detection of specific Cryptosporidium coproantigens (Cho et al 2012;Mirhashemi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation